MRI contrast agent for targeting glioma: interleukin-13 labeled liposome encapsulating gadolinium-DTPA. Issue 5 (31st October 2015) - Liu, Xiaoli; Madhankumar, Achuthamangalam B.; Miller, Patti A.; Duck, Kari A.; Hafenstein, Susan; Rizk, Elias; Slagle-Webb, Becky; Sheehan, Jonas M.; Connor, James R.; Yang, Qing X.
Abstract: Background: Detection of glioma with MRI contrast agent is limited to cases in which the blood-brain barrier (BBB) is compromised as contrast agents cannot cross the BBB. Thus, an early-stage infiltrating tumor is not detectable. Interleukin-13 receptor alpha 2 (IL-13Rα2), which has been shown to be overexpressed in glioma, can be used as a target moiety. We hypothesized that liposomes conjugated with IL-13 and encapsulating MRI contrast agent are capable of passing through an intact BBB and producing MRI contrast with greater sensitivity. Methods: The targeted MRI contrast agent was created by encapsulating Magnevist (Gd-DTPA) into liposomes conjugated with IL-13 and characterized by particle size distribution, cytotoxicity, and MRI relaxivity. MR image intensity was evaluated in the brain in normal mice post injection of Gd-DTPA and IL-13-liposome-Gd-DTPA one day apart. The specificity for glioma detection by IL-13-liposome-Gd-DTPA was demonstrated in an intracranial glioma mouse model and validated histologically. Results: The average size of IL-13-liposome-Gd-DTPA was 137 ± 43 nm with relaxivity of 4.0 ± 0.4 L/mmole-s at 7 Tesla. No significant cytotoxicity was observed with MTS assay and serum chemistry in mice. The MRI signal intensity was enhanced up to 15% post injection of IL-13-liposome-Gd-DTPA in normal brain tissue following a similar time course as that for the pituitary gland outside of the BBB. MRI enhanced by IL-13-liposome-Gd-DTPA detected small tumor masses in addition to those seen with Magnevist-enhanced MRI. Conclusions: IL-13-liposome-Gd-DTPA is able to pass through the uncompromised BBB and detect an early stage glioma that cannot be seen with conventional contrast-enhanced MRI.